EFFECT OF HUMIC ACID AND CYCOCEL (CCC) ON GROWTH AND FLOWERING OF Pelargonium X hortorum (Mesopotamia Journal of Agriculture)
The experiment were performed in the traditional house that belongs to the Department of Horticulture and landscape design / College of Agriculture and Forests /University of Mosul from the period between the 1th of Nov. 2010 to the 20th. Of June 2011. The aim is to study the effect of some agricultural factors on growth and flowering of Pelargonium X hortorum L.H.Bailey known as Zonal, cv. Hidemi. The experiment included studing the effect of fertilization with Humic acid with 0, 3.5, and 5.25 mg/liter and spraying the Vegetative growth with Cycocel 0, 1500 and 3000 mg/liter .Factorial experiment was implemented by using the Factorial Experiment in Complete Randomized Design with three replicates and six plants for each. The results have shown the following: Fertilizing Humic acid with a concentration of 3.5 mg/liter led to a significant increase in plant height 9.088 cm, leaves number 15.943 leaf/plant and leaf area 241.083 cm2 /plant compared with control, in addition an increase in the number of inflorescence and the number of florets in the inflorescence. The highest values Anthosyanine found in plant that fertilized with Humic acid 5.25 mg/liter, These values are significantly different from those obtained at fertilizing Humic acid with a concentration of 3.5 mg/liter.Spraying with any of the Cycocel concentrations led to a significant reduction in the plant height. A significant increase in the number of leaves formed on the plant add chlorophyll in leaves was noticed as well when sprayed with the two used concentrations.Generally speaking, it could be said that the plants fertilized with Humic acid at a concentration of 3.5 mg/liter interaction with spraying with Cycocel at a concentration of 1500 and 3000 mg/liter had the advantage of obtaining the largest number of leaves besides an increase in the number of inflorescence up to 2.833 inflorescence /plant. On the other hand, fertilizing with Humic acid at a concentration of 3.5 mg/lite interaction with Cycocel at a concentration of 3000 mg/liter caused an increase in the Anthosyanine concentration in flowers up to 60.810 mg/100 g wet weight.